Maternal and perinatal outcomes of indicated inductions of labor. (17th July 2016) - Magann, Everett F.; Ounpraseuth, Songthip T.; Miller, Christina D.; Novotny, Sarah A.; Lee, Nicole M.; Greenfield, William W.; Morrison, John C.
Abstract: Purpose : The purpose of this study was to evaluate the labor characteristics and maternal/perinatal consequences following indicated induction of labor. Methods : This retrospective study examined all of the indicated inductions over 24 months and at two institutions evaluated mode of delivery (vaginal versus cesarean) as well as a comprehensive list of labor characteristics and maternal/perinatal outcomes. Results : There were 1577 indicated inductions with 1097/1577 (69.6%) delivering vaginally. Women with a cesarean delivery had lower parity ( p  < (0).0001) and Bishop's score ( p  < (0).0001), and higher body mass indices ( p  = 0.022). Indication for induction due to preeclampsia increased the risk of a cesarean delivery ( p  = 0.008). Chorioamnionitis, post-partum complications and NICU admissions were greater in the women delivered by cesarean section. Conclusions : Indicated inductions which result in cesarean delivery were more likely in women with higher body mass indexes, lower parity, and Bishops scores, as well as preeclampsia.